2022
DOI: 10.1016/j.joca.2021.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis for quantification of knee joint space width with weight-bearing CT: comparison with non-weight-bearing CT and weight-bearing radiography

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In this study, data were gathered under non-weightbearing conditions. For example, varus/valgus rotation is significantly different in a weightbearing versus non-weightbearing situation [30]. As a result, values found in this study cannot be extrapolated to a weightbearing situation.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, data were gathered under non-weightbearing conditions. For example, varus/valgus rotation is significantly different in a weightbearing versus non-weightbearing situation [30]. As a result, values found in this study cannot be extrapolated to a weightbearing situation.…”
Section: Discussionmentioning
confidence: 58%
“…non-weightbearing CT or weightbearing radiographs. 59 Weightbearing also affects tibiofemoral kinematics. With quadriceps muscle contraction and joint loading, the result is progressive internal tibiofemoral rotation and a decrease in the TT-TG distance.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…For example, Fritz et al 60 reported bone-on-bone apposition in 25% of tibiofemoral compartments using WBCT, in comparison with only 8% and 10%, respectively, on fixed-flexion radiographs (FF-XR) and supine CT. Studies to date, comparing FF-XR and WBCT with MRI have revealed that the sensitivity, accuracy, and predictive value for detecting osteophytes and subchondral cysts is higher on WBCT than on FF-XR; 58 2D JSW on FF-XR poorly correlates with MRI cartilage damage; 61 3D joint space width (JSW) on WBCT correlates better than FF-XR with cartilage damage; 62 and responsiveness of change in 3D JSW on WBCT over 24 months is significantly higher than that for radiographic or MRI biomarkers. In addition to 3D JSW on WBCT being more sensitive and responsive to tibiofemoral changes, using articular cartilage morphology on MRI as the referent standard, tibiofemoral 3D JSW on WBCT correlated more highly than FF-XR minimal JSW; 62 and sensitivity and accuracy for patellofemoral cartilage lesions was significantly higher on WBCT than on FF-XR.…”
Section: Weight-bearing Knee Ct In Oa Imagingmentioning
confidence: 99%